Diskursus Kepemimpinan Pemerintahan Kontemporer - Nas, Jayadi (Program Studi Ilmu Pemerintahan Fisip Unhas, 2015)
Abstract: This article outlines two things: first, the concept of leadership that includes the causal emergence of leaders and leadership requirements; and secondly, the concept of governance includes the debate whether or not the government and the various forms of contemporary governance. As a result, the governments leadership in an area of government is determined by the capabilities possessed by every leader. Capability in question is the ability of the government in implementing the tasks according to the needs and interests of its people and the demands of a global society. It takes the ability of a leader to understand the aspirations of its people and read the trend of the times are constantly changing.Keywords: leadership, government, transitional regimeÂ Abstrak: Artikel ini menguraikan dua hal: pertama, konsep kepemimpinan yang meliputi sebab-musabab munculnya pemimpin dan syarat-syarat kepemimpinan; dan kedua, konsep pemerintahan yang meliputi perdebatan perlu tidaknya pemerintahan dan berbagai bentuk pemerintahan kontemporer. Hasilnya, kepemimpinan pemerintahan dalam suatu wilayah pemerintahan sangat ditentukan oleh kapabilitas yang dimiliki oleh setiap pemimpin. Kapabilitas yang dimaksud adalah kemampuan dalam melaksanakan tugas pemerintahan yang sesuai dengan kebutuhan dan kepentingan rakyatnya serta tuntutan masyarakat global. Dibutuhkan kemampuan seorang pemimpin dalam memahami aspirasi rakyatnya dan membaca kecenderungan zaÂ¬man yang terus berubah.Kata kunci: kepemimpinan, pemerintahan, transisi rezim